Lessons learned from a community engagement initiative within Irish higher education. Issue 1 (2nd January 2018) - Quillinan, Bernie; McEvoy, Eileen; MacPhail, Ann; Dempsey, Ciara
Abstract : This paper focuses on a community–university partnership built around a programme of study co-created by residents of a disadvantaged community and situated, for the most part, within that community. The aim of this paper is to share lessons learned from this community engagement initiative, as identified through a research study which ran concurrent to the programme. The study involved 41 interviews (18 individual interviews and 23 focus groups) over a two-year period with 28 participants. Participants included students, lecturers and community and university stakeholders. The finding section focuses on the characteristics of the initiative which allowed it to positively impact those involved. The data indicated that (i) the authenticity of the partnership between the community and university, (ii) the suitability of the lecturers and (iii) the ability of the lecturers and management to adapt the programme to identified needs were all key to the success of the programme. The paper concludes with a discussion, incorporating relevant literature, regarding what can be learned from this programme for those interested in enacting truly engaged practice in Irish higher education.